Inclusive wealth index measuring sustainable development potentials for Chinese cities. (January 2022) - Cheng, Danyang; Xue, Qianyu; Hubacek, Klaus; Fan, Jingli; Shan, Yuli; Zhou, Ya; Coffman, D' Maris; Managi, Shunsuke; Zhang, Xian
Highlights: Results highlight the considerable regional disparities in China. Cities in East China show high levels and increasing capacities for sustainability. Cities in the north cluster will lag behind in individual welfare in the long term. Energy-producing cities will follow unsustainable pathways without strong policies. Abstract: The UN Sustainable Development Goals (SDGs) are the blueprint to achieve a better and more sustainable future. To achieve the goal, tracking progress — not just on a national level, but locally — is crucial to guide future policy development. While sustainability assessment at the national evel is quite advanced in China, similar assessments focusing at the regional or even at the city-level are currently lacking. Here, we advanced the Inclusive Wealth Index (IWI) framework, which is firstly proposed by the United Nations Development Programme, through taking water wealth into account and adjusting the variable based on data availability. Then we investigate the sustainability performance of 210 cities in China in 2016 via the advanced version of the IWI framework. The analysis makes a holistic assessment based on produced, human, and natural capital, as well as considering heterogeneities in economy, social, and environmental conditions across these cities. We find that cities clustered in the eastern parts of China are characterized by high levels of sustainability performance and increasing capacities for sustainability, largely driven by their high quality and quantity of human capital. In comparison, the western cities have a large amount of low-skilled human capital and low levels of produced capital, which determines their low sustainability performance. Cities clustered in the north are heavily dependent on low value-added products and resource-intensive industries. Furthermore, we make projections of the IWI and its three components for different cities from 2020 to 2030, referring to the index systems presented in city planning which describe the development speed of income, education, fixed asset investment, forests etc. In the future, cities in central and western clusters show considerable potential for increasing IWI per capita, whereas cities with a dominant energy sector in the north would face declining capacity for sustainability due to the exhaustion of fossil fuels and raw materials. By fully taking account of and adapting to local circumstances, we tailor-design pathways for different types of cities to grow their sustainability potentials. Those resources-dependent cities in the north could avoid the impending decline by gradually developing their human and produced capital while abandoning their resource dependency. Our study contributes to city-level sustainable development in China through the lens of per capita IWI and the potential future dynamics of changing compositions in their capital.